DEVELOPMENT OF CREATIVE ABILITIES OF THE FUTURE TEACHER IN THE PROCESS OF HIGHER EDUCATION - Kazanji, O.V. (Pedagogy of Higher and Secondary Education, 2009)
In this article the essence of pedagogical creative works is considered some qualities of creative teacher are defined and the experimental methodic of development of future teachers creative abilities during university training is revealed.